Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Kantor Pos Kcu Solo - Dirga Aji Saputra; Ari Susanti (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Abstract: This study aims to analyze the effect of service quality on customer satisfaction at the Solo Main Post Office (KCU Solo). The background of this research is driven by the increasing competition within Indonesia’s logistics service industry and the need for service innovation in public institutions to adapt to the demands of modern customers. This research employs a quantitative method by distributing structured questionnaires to active users of postal delivery services. The collected data were analyzed using simple linear regression to examine the relationship between service quality and customer satisfaction. The results indicate that service quality is a key determinant of customer satisfaction, particularly in terms of reliability, responsiveness, and assurance. These findings affirm that improving service quality enhances customer trust and satisfaction toward postal services. The study provides managerial implications for PT Pos Indonesia to continuously improve service innovation, employee responsiveness, and facility convenience in order to maintain competitiveness in the era of digital transformation. Keywords: Customer Satisfaction; Service Quality; Postal Service; PT Pos Indonesia; SERVQUAL